2016
DOI: 10.1371/journal.ppat.1006043
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose-6-Phosphate-Mediated Toxicity Determines Essentiality of OtsB2 in Mycobacterium tuberculosis In Vitro and in Mice

Abstract: Trehalose biosynthesis is considered an attractive target for the development of antimicrobials against fungal, helminthic and bacterial pathogens including Mycobacterium tuberculosis. The most common biosynthetic route involves trehalose-6-phosphate (T6P) synthase OtsA and T6P phosphatase OtsB that generate trehalose from ADP/UDP-glucose and glucose-6-phosphate. In order to assess the drug target potential of T6P phosphatase, we generated a conditional mutant of M. tuberculosis allowing the regulated gene sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 50 publications
1
48
0
Order By: Relevance
“…In the mouse model of active tuberculosis the OtsAB2 pathway, which generates trehalose from glucose and glucose-6-phosphate, is the dominant pathway required for M. tuberculosis growth and virulence (Murphy et al, 2005). However, recent studies revealed that essentiality of OtsB2 gene in vivo for the acute infection is due to self-poisoning of knock-outed cells by accumulation of trehalose-6-phosphate (Korte et al, 2016). Inactivation of the second (TreYZ) pathway, which generates trehalose from α-1,4-linked glucose polymers, had no effect on the growth of M. tuberculosis in mice (Murphy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse model of active tuberculosis the OtsAB2 pathway, which generates trehalose from glucose and glucose-6-phosphate, is the dominant pathway required for M. tuberculosis growth and virulence (Murphy et al, 2005). However, recent studies revealed that essentiality of OtsB2 gene in vivo for the acute infection is due to self-poisoning of knock-outed cells by accumulation of trehalose-6-phosphate (Korte et al, 2016). Inactivation of the second (TreYZ) pathway, which generates trehalose from α-1,4-linked glucose polymers, had no effect on the growth of M. tuberculosis in mice (Murphy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We then utilised a promoter replacement strategy to demonstrate the essentiality of Rv2509 in slow‐growing mycobacterial vaccine strain Mycobacterium bovis BCG. The P myc1 promoter from M. smegmatis engineered to contain four tetO operator sites (Korte et al, ) was inserted immediately upstream of the start codon of BCG2529, the Rv2509 homologue in M. bovis BCG‐Pasteur, using Specialised Transduction generating the strain BCG::P Tet ‐ BCG2529 . Controlled gene expression of the BCG2529 gene was achieved using a plasmid‐borne synthetic gene ( rev‐tetR ) derived from Tn10 tetR encoding a mutated TetR protein with reversed binding affinity to tetO sites upon the binding of tetracycline.…”
Section: Resultsmentioning
confidence: 99%
“…For establishing the regulated expression of the BCG2529 gene, a synthetic gene cassette ( hyg ‐P myc1 ‐4X tetO ) comprising a hygromycin‐resistance gene and the P myc1 promoter from M. smegmatis engineered to contain four tetO operator sites (Korte et al, ) was inserted immediately upstream of the BCG2529 start codon in M. bovis BCG‐Pasteur. Targeted gene knock‐in was achieved by specialised transduction employing temperature‐sensitive mycobacteriophages essentially as described previously (Korte et al, ). Briefly, for the generation of an allelic exchange construct for site‐specific insertion of the hyg ‐P myc1 ‐4X tetO cassette in M. bovis BCG‐Pasteur, upstream‐ and downstream DNA regions flanking the BCG2529 start codon were amplified by PCR employing the oligonucleotide pairs Mb2537 _LL 5′‐TTTTTCCATAAATTGGAACCGCTACCTGACATGAAACCC‐3′ and Mb2537 _LR 5′‐TTTTTCCATTTCTTGGGCCGATGTTCTGCGAAGCCCCGG‐3′ as well as Mb2537 _RL 5′‐TTTTTCCATAGATTGGATGCCGATACCCGCGCCCAGCCC‐3′ and Mb2537 _RR 5′‐TTTTTCCATCTTTTGGCGGTGTGGGAGGAGATACTCAAG‐3′ respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the treYZ pathway, another 4 additional pathways of trehalose biosynthesis have been observed in prokaryotes, plants, fungi, and nonvertebrate animals. Among those other pathways, the so-called osmotically regulated trehalose synthesis (ots)AB pathway has attracted particular attention as a target of interest for therapeutic intervention in infectious diseases [reviewed in Cross et al (12)] because accumulation of the metabolite trehalose 6-phosphate (T6P) results in a lethal phenotype in Caenorhabditis elegans and Mycobacterium tuberculosis (13,14).…”
mentioning
confidence: 99%